2021
DOI: 10.31014/aior.1993.04.03.324
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the Flipped Learning Pedagogy in Thai Undergraduate Education

Abstract: The world is changing at a much faster pace than in the past and has become more connected than ever before. This has led to increasing levels of economic competition and socio-political-cultural transformation. The necessity for Thailand to compete internationally is based on the creation of quality graduates. The rapid changes in Information and Communication Technology (ICT) are transforming the ways people think, live, learn, and interact. These rapid changes have implications in all spheres of national de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Kevin Fuchs proved the positive impact of virtual whiteboards on the level of students' engagement while learning. Although the research did not show any drawbacks of e-learning, it revealed a correlation between the level of engagement and the year of study, which is the primary implication of the study (Fuchs, 2021). Pazilova Nasibaxon Muhammadqosimovna and Usmonova Dona Satvoldiyevna also mentioned no disadvantages to whiteboard use.…”
Section: Scientific Literature Reviewmentioning
confidence: 75%
“…Kevin Fuchs proved the positive impact of virtual whiteboards on the level of students' engagement while learning. Although the research did not show any drawbacks of e-learning, it revealed a correlation between the level of engagement and the year of study, which is the primary implication of the study (Fuchs, 2021). Pazilova Nasibaxon Muhammadqosimovna and Usmonova Dona Satvoldiyevna also mentioned no disadvantages to whiteboard use.…”
Section: Scientific Literature Reviewmentioning
confidence: 75%